Media poster sebagai sarana edukasi masyarakat dalam upaya pencegahan covid-19 - Masruroh Masruroh; Nur Hayati (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
The outbreak of Covid-19 led the government to do some preventive action such as the promotion of health protocol and healthy lifestyle. Unfortunately, some people still ignoring the current importance of this preventive action. We need to educate them about the importance of this preventive action using alternative media such as posters. The purpose of this activity is to find poster’s eligibility as a media to educate people of Dlanggu Village about preventive action to Covid-19. There are three stages done in this activities. They are preparation, implementation, and evaluation stage. The design of poster have been successfully made in this activity with an average score of 3.5. The result showed, in general, this poster was a good media to educate people about health protocol and healthy lifestyle during covid-19 pandemics.